Origin and Evolution of Eocene Rock Salts in Pakistan and Implications for Paleoclimate Studies: Insights From Chemistry and Cl Stable Isotopes - Hussain, Syed Asim; Han, Feng Qing; Ma, Zhe; Hussain, Amjad; Mughal, Muhammad Saleem; Han, Jibin; Alhassan, Abdullah; Widory, David (Frontiers in Earth Science, 2021)
directly recorded the closure of the Tethys Sea and the Himalayan collision between India, Asia, and a number of other small plates. During the Eocene, after the collision between the Indian and Eurasian plates terminated the Tethys Sea, thick-bedded marine evaporite sequences developed in the KB. In this study, we combined mineralogy, geochemistry, fluid inclusion and chlorine stable isotope compositions to discuss the origin and evolution of the KB Eocene halite deposits with the ultimate objective of defining the paleoclimate that was prevailing in Asia during the Eocene. Our results showed that halite samples were SO42- rich (225- 370.103 ppm) and Br- poor (<3ppm). Cl-, B+, Mg2+, K+, SO42- and very low Br concentrations as well as the (Br/Cl) ratios indicated that halite resulted of a mixture of solutions with variable compositions and that dissolution, recrystallization and a progressive decrease in dolomitization were the mechanisms leading to the formation of these evaporites. A Br/Cl vs Cl plot revealed that the end members involved were: seawater (SW), saline waters and/or freshwaters. The recrystallization process prevented identifying the primary structures and primary fluid-inclusions. Most of Cl isotope compositions (-0.54‰<37Cl<0.83‰) were within the usual range (0±0.5‰) associated to seawater as the initial source for the halite. The higher isotope compositions (37Cl≥0.83‰) comforted the hypothesis of the genesis by mixing of solutions of different origins as well as the involvement of recrystallization. Based on our results, we are proposing the following to explain the regional paleoclimate sequence: (1) shallow water conditions; (2) halite precipitation induced by evaporation, (3) unstable paleoclimatic conditions that resulted in the morphing from an evaporite basin into a terrestrial foreland basin. All these events were controlled by regional tectonic and linked to both the overall uplift times of the NW Indian Craton and the Eocene thermal maximum 1 during the Eocene-Oligocene period.